Functional septorhinoplasty alters brain structure and function: Neuroanatomical correlates of olfactory dysfunction - Whitcroft, Katherine L.; Mancini, Laura; Yousry, Tarek; Hummel, Thomas; Andrews, Peter J. (Frontiers in Allergy, 2023)
Introduction We previously demonstrated functionally significant structural plasticity within the central olfactory networks, in association with improved olfaction after surgical treatment of chronic rhinosinusitis (CRS). In order to confirm and expand on these findings, the primary aim of this study was to determine whether these same regions undergo functionally significant structural plasticity following functional septorhinoplasty (fSRP), in patients with non-CRS olfactory dysfunction (OD) of mixed cause. fSRP has previously been shown to improve olfactory function, and the secondary aim of this study was to provide initial insights into the mechanism by which fSRP affects olfaction. Methods We performed a pilot prospective, multimodal neuroimaging study in 20 participants undergoing fSRP, including patients with non-CRS OD of mixed cause, as well as normosmic surgical controls. Participants underwent psychophysical olfactory testing, assessment of nasal airway, structural and functional neuroimaging. This was performed pre- and postoperatively in patients, and preoperatively in controls. Results There was a statistically and clinically significant improvement in mean psychophysical olfactory scores after surgery. This was associated with structural and functional plasticity within areas of the central olfactory network (anterior cingulate, orbitofrontal cortex, insula, temporal pole). Improved psychophysical scores were significantly correlated with change in bilateral measures of nasal airflow, not measures of airflow symmetry, suggesting that improved overall airflow was more important than correction of septal deviation. Conclusion This work highlights the importance of these neuroanatomical regions as potential structural correlates of olfactory function and dysfunction. Our results also provide initial insight into the mechanistic effects of fSRP on olfaction. Further work could investigate the utility of these regions as personalised biomarkers of OD, as well as the role of fSRP in treating OD.